Topical application of lectin Artin M improves wound healing in defects created in the palatal mucosa: an in vivo study in dogs - Kim, Yeon Jung [UNESP]; de Molon, Rafael Scaf [UNESP]; da Silva, Vanessa Camila; da Veiga Conrado, Marina Cavalcanti Albuquerque; Spolidório, Luis Carlos [UNESP]; Roque-Barreira, Maria Cristina Antunes; Cirelli, Joni Augusto [UNESP] (Springer Nature, 2020)
Previous studies have shown that topical application of lectin Artin-M accelerates wound healing in the rat oral mucosa. The aim of this study was to evaluate, by means of histology and immunohistochemistry (IHC) the effects of Artin-M on wound healing in the palatal mucosa in dogs. Three full thickness wounds of 6 mm diameter were surgically created in the palatal mucosa of twenty dogs and randomly divided into three groups according to one of the treatment assigned: Group C—Control (coagulum); Group A—Artin-M gel; Group V—Vehicle (carboxymethylcellulose 3%). Each animal received all the three experimental treatments. Afterwards, four animals were killed at 2, 4, 7, 14 and 21 days post-surgery. Wounded areas were photographed and scored for macroscopic evaluation. Biopsies were harvested and used for descriptive histological analysis, proliferating cell nuclear antigen IHC and measurement of myeloperoxidase activity. The results demonstrated faster wound closure in group A in comparison to the other groups in all the periods evaluated. Histological analyses exhibited improved re-epithelialization and collagen fiber formation resulting in faster maturation of granulation tissue in group A compared to the other groups by day 14. Treatment with Artin-M gel significantly induced cell proliferation and increased volumetric density of fibroblasts at day 2 and 4 (p < 0.05). Neutrophil infiltration in group A was significantly higher than the other groups (p < 0.05) at the same time points. Collectively, our findings demonstrated that Artin-M may potentially favor wound healing on palatal mucosa lesions via recruitment of neutrophils and promotion of cell proliferation.
Keywords: Animal model; Lectin; Oral mucosa; Palate; Wound healing